Composite molding sheet for filling

Through the combination of nano-reinforced materials and shape memory polymers, the gradient structure and intelligent responsiveness are designed, which solves the problem that traditional dental molded sheets cannot simulate tooth convexity, and realizes the efficiency, stability and adaptation of composite molded sheets in dental restoration. It avoids subsequent dressing and polishing.

CN119119519APending Publication Date: 2024-12-13SUZHOU STOMATOLOGICAL HOSPITAL (GRP) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411204861.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-30
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Traditional dental molding sheets cannot effectively simulate the natural convexity of teeth, resulting in the repaired teeth being prone to food impaction and fracture of filling materials.

Method used

Using composite molded sheets that combine nano-reinforced materials with shape memory polymers, the gradient structure and intelligent responsiveness are designed through ultrasonic dispersion, mixing, injection molding and multi-stage crosslinking treatment to ensure that the material responds quickly and accurately under light and mild conditions. Restore shape.

Benefits of technology

The performance consistency and reliability of composite materials in multiple cycles is achieved, the adaptability of the material and the stability of the recovery process are improved, and the need for subsequent dressing and polishing is avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119519A_ABST
    Figure CN119119519A_ABST
Patent Text Reader

Abstract

The invention discloses a composite molded sheet for filling, which is prepared by the following steps: mixing nano reinforced material particles with a solvent, and carrying out ultrasonic dispersion treatment to obtain a nano reinforced material solution; selecting a water-swellable material, preparing the water-swellable material into a pre-polymerized solution, mixing and stirring the pre-polymerized solution with the nano reinforced material to obtain a base material, adding the shape memory polymer, and continuously stirring to obtain a mixture; adding an intelligent response substance into the mixture, and continuously stirring, so that the mixture can sense the change of the environment and then change, thereby obtaining an intelligent response mixture; carrying out curing treatment on the intelligent response mixture under UV illumination and at 60-80 DEG C to obtain a composite molding sheet; the shape is more stable and accurate in the recovery process, and powerful support is provided for application of the composite material in a complex environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a field related to medical instruments, and in particular to a composite forming sheet for filling. Background Art

[0002] The history of dental molding sheets can be traced back to the mid-20th century. Initially, traditional molding sheets were mostly flat and thick, which could not simulate the natural convexity of teeth well, resulting in problems such as food impaction and fracture of filling materials after restoration. With the continuous development of materials science and oral medicine, a new type of molding sheet, the segmented molding sheet (such as the Palodent system), came into being. This molding sheet is exquisitely designed and has a certain convexity, which can better simulate the natural shape of teeth, thereby improving the restoration effect. The main function of the molding sheet is to help doctors form the correct adjacent relationship and anatomical morphology during tooth restoration. The anatomical morphology of the adjacent surfaces of teeth has a certain convexity, which can not only better form a close adjacent relationship, but also guide the food during chewing, maintain the tension of the gums, and prevent food impaction. Because traditional molding sheets cannot simulate this convexity, the restoration effect is not ideal. After the restoration process is completed, trimming is required to grind off the excess protrusions. Summary of the invention

[0003] The present invention overcomes the shortcomings of the prior art and provides a composite forming sheet for filling.

[0004] To achieve the above object, the technical solution adopted by the present invention is: a composite forming sheet for filling, comprising the following steps:

[0005] S1: mixing nano-reinforcement material particles with a solvent and performing ultrasonic dispersion treatment to obtain a nano-reinforcement material solution;

[0006] S2: Select a material that swells when exposed to water, prepare it into a prepolymer solution, mix it with a nano-reinforced material, stir it to obtain a matrix material, add a shape memory polymer and continue stirring to obtain a mixture;

[0007] S3: adjusting the ratio of nano-reinforced material particles, prepolymer liquid and shape memory polymer in the mixture, injecting them into the mold through injection molding technology to obtain a gradient mixture, and performing cross-linking treatment;

[0008] S4: adding a smart response substance to the mixture and continuously stirring the mixture so that the mixture can sense changes in the environment and then change, thereby obtaining a smart response mixture;

[0009] S5: Curing the smart response mixture under UV light at 60-80° C. to obtain a composite molded sheet.

[0010] In a preferred embodiment of the present invention, in S1, the nano-reinforcement material particles are selected from one or more of nano-silicon dioxide, nano-cellulose or nano-clay, the solvent is selected from one or more of isopropanol weak alkaline aqueous solution or methanol, the ratio of nano-particles to solvent is 1:10-30, and the ultrasonic dispersion treatment time is 30-60 min.

[0011] In a preferred embodiment of the present invention, in S2, the water-swellable material is selected from one or more of polyacrylamide, calcium carbonate or barium carbonate, the amount of nano-reinforced material added is 10%-20% of the total volume of the prepolymer, the stirring speed is 800-1000rpm, and the time is 20-40min.

[0012] In a preferred embodiment of the present invention, in S2, the preparation of the prepolymer solution is specifically to mix the water-swellable material with a solvent and a catalyst, and to carry out a polymerization reaction under stirring.

[0013] In a preferred embodiment of the present invention, the solvent is selected from one or more of ethanol, dilute nitric acid or hydrochloric acid, the catalyst is selected from one or more of ammonium sulfate, alkaline catalyst or acid catalyst, the stirring speed is 800-1000rpm, and the time is 30-60min.

[0014] In a preferred embodiment of the present invention, in S2, the shape memory polymer is selected from one or more of styrene-based shape memory polymer, polyimide-based shape memory polymer or cyanate-based shape memory polymer, wherein the added amount of the shape memory polymer is 20%-30% of the base material.

[0015] In a preferred embodiment of the present invention, in S4, the smart responder is one or more of a pH-responsive polymer and a temperature-responsive hydrogel, wherein the smart responder accounts for 5%-10% of the volume of the mixture.

[0016] In a preferred embodiment of the present invention, in S3, the ratio of nano-reinforcement material particles-prepolymer liquid-shape memory polymer is 1-10:3-7:1-5.

[0017] In a preferred embodiment of the present invention, in S3, the mold includes a cavity and a placeholder plate plugged into the cavity, an elliptical cavity with a flat cross-section is provided inside the cavity, and the placeholder plate is arranged at the center of the cavity.

[0018] In a preferred embodiment of the present invention, in S3, the multi-stage cross-linking treatment is specifically:

[0019] Primary cross-linking treatment: Place the mixture in an oven and heat it to 40-60°C for 1-2 hours;

[0020] Secondary cross-linking treatment: Place the mixture after primary cross-linking in a vacuum oven and heat it to 60-80°C for 4-8 hours.

[0021] The present invention solves the defects existing in the background technology and has the following beneficial effects:

[0022] (1) The present invention provides a composite forming sheet for filling. By designing the concentration of the composite material to be gradient, the high-concentration photosensitive shape memory polymer on the surface is combined with the nanomaterial, so that the composite material can accurately remember the current shape during the deformation process, and quickly and accurately restore to the original state after the light stops or the stimulus is removed. This high degree of stability ensures the consistency and reliability of the performance of the composite material in multiple cycles, providing a solid guarantee for the application of smart materials. At the same time, by utilizing the concentration difference between the surface and internal materials, the composite material can more flexibly adapt to changes in the external environment during expansion and recovery. This gradient effect not only improves the adaptability of the material, but also ensures that the shape is more stable and accurate during the recovery process, providing strong support for the application of composite materials in complex environments.

[0023] (2) The present invention provides a composite forming sheet for filling, which quickly initiates primary cross-linking under mild conditions to build a preliminary but stable cross-linking bridge between polyacrylamide and shape memory polymer, and enters the secondary cross-linking stage. Long-term curing in a high-temperature vacuum environment becomes a catalyst, which not only deepens the level and strength of the cross-linking network, but also removes all impurities and bubbles that may interfere with shape memory through vacuum technology. More importantly, the close connection between the shape memory polymer and polyacrylamide greatly promotes the interaction between the two, so that the composite material can respond with unprecedented speed and accuracy when subjected to specific stimuli, and accurately restore to the preset shape. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art are briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For those of ordinary skill in the art, other drawings can be obtained based on these drawings without creative work.

[0025] Figure 1 It is a three-dimensional structural diagram of a preferred embodiment of the present invention. DETAILED DESCRIPTION

[0026] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein. Therefore, the protection scope of the present invention is not limited to the specific embodiments disclosed below.

[0028] As shown in the figure, a composite forming sheet for filling includes the following steps:

[0029] S1: mixing nano-reinforcement material particles with a solvent and performing ultrasonic dispersion treatment to obtain a nano-reinforcement material solution;

[0030] In a preferred embodiment of the present invention, in S1, the nano-reinforcement material particles are selected from one or more of nano-silicon dioxide, nano-cellulose or nano-clay, the solvent is selected from one or more of isopropanol weak alkaline aqueous solution or methanol, the ratio of nano-particles to solvent is 1:10-30, and the ultrasonic dispersion treatment time is 30-60 min.

[0031] It should be noted that the nano-reinforced material is dispersed in a suitable amount of solvent and treated with an ultrasonic disperser for 30 minutes to 1 hour to ensure that the nano-material is evenly dispersed without agglomeration, thereby improving the overall performance of the composite material.

[0032] S2: Select a material that swells when exposed to water, prepare it into a prepolymer solution, mix it with a nano-reinforced material, stir it to obtain a matrix material, add a shape memory polymer and continue stirring to obtain a mixture;

[0033] In a preferred embodiment of the present invention, in S2, the water-swellable material is selected from one or more of polyacrylamide, calcium carbonate or barium carbonate, the amount of nano-reinforced material added is 10%-20% of the total volume of the prepolymer, the stirring speed is 800-1000rpm, and the time is 20-40min.

[0034] In a preferred embodiment of the present invention, in S2, the preparation of the prepolymer liquid is specifically to mix the water-swellable material with a solvent and a catalyst, and carry out a polymerization reaction under stirring; the solvent is selected from one or more of ethanol, dilute nitric acid or hydrochloric acid, the catalyst is selected from one or more of ammonium sulfate, an alkaline catalyst or an acid catalyst, the stirring speed is 800-1000rpm, and the time is 30-60min.

[0035] It should be noted that, in order to prepare PAM (polyacrylamide) gel as the matrix of the composite material through polymerization reaction, the PAM monomer, solvent and catalyst are mixed uniformly in a predetermined ratio, and the polymerization reaction is carried out under stirring conditions to generate gel, and the treated nano-reinforced material is evenly dispersed in the PAM prepolymer solution to enhance the mechanical properties and functional properties of the composite material, and stirring is continued to ensure that the nano-material is evenly dispersed in the PAM matrix to avoid local agglomeration. Polyacrylamide is easily soluble in cold water and can form gel under certain conditions. This property makes it an ideal matrix material in composite materials, which can absorb and retain a large amount of water, so that it expands and deforms when it encounters water, and it has a good thickening effect, which can increase the viscosity of the composite material and improve its processing performance. At the same time, it can also stabilize suspended particles, prevent particle precipitation and stratification, and ensure the uniform distribution of the various components of the composite material. By introducing nano-reinforced materials, the polyacrylamide matrix can form a more solid and stable network structure, thereby improving the mechanical strength, wear resistance and corrosion resistance of the composite material. Through primary cross-linking and secondary cross-linking treatment, the polyacrylamide matrix can be further solidified and form a more solid bond with other components. This multi-stage cross-linking process ensures the stability and reliability of the composite material in complex environments.

[0036] In a preferred embodiment of the present invention, in S2, the shape memory polymer is selected from one or more of styrene-based shape memory polymer, polyimide-based shape memory polymer or cyanate-based shape memory polymer, wherein the added amount of the shape memory polymer is 20%-30% of the base material.

[0037] It should be noted that the shape memory polymer (SMP) is mixed with the PAM gel to prepare a composite material with shape memory function. SMP particles or prepolymer solution are added to the PAM gel containing the nano-reinforced material, and the mixture is stirred evenly using a mechanical stirrer or a high shear mixer to ensure that the SMP and the PAM gel are fully mixed.

[0038] S3: adjusting the ratio of nano-reinforced material particles, prepolymer liquid and shape memory polymer in the mixture, injecting them into the mold through injection molding technology to obtain a gradient mixture, and performing cross-linking treatment;

[0039] In a preferred embodiment of the present invention, in S3, the ratio of nano-reinforcement material particles-prepolymer liquid-shape memory polymer is 1-10:3-7:1-5.

[0040] In a preferred embodiment of the present invention, in S3, the mold includes a cavity and a placeholder plate plugged into the cavity, an elliptical cavity with a flat cross-section is provided inside the cavity, and the placeholder plate is arranged at the center of the cavity.

[0041] It should be noted that a gradient structure is formed by controlling the distribution of SMP and nano-reinforced materials in the composite material. Injection molding technology is used to control the distribution of SMP and nano-reinforced materials in the composite material. The surface layer is designed to be a high-concentration layer rich in photosensitive SMP and nano-materials to improve the response speed and mechanical properties of the composite material; the interior is a low-concentration layer mainly composed of PAM gel to reduce cost and weight. The surface layer is rich in photosensitive shape memory polymers, which makes the composite material more sensitive and rapid in response to light. Under light conditions, the photosensitive polymer can quickly undergo photo-crosslinking or photo-induced deformation, thereby driving the entire composite material to deform. The introduction of nanomaterials (nano-silica, nano-cellulose) not only enhances the mechanical properties of the composite material, but also improves its absorption and conversion efficiency of light. The synergistic effect of nanomaterials and photosensitive polymers further improves the responsiveness of the composite material under light. The photosensitive shape memory polymer on the surface can remember the current shape and expansion degree during the deformation process. When the light stops or the stimulus is removed, the composite material can return to the memorized shape and state. This stable shape memory effect allows the composite material to maintain consistent performance during multiple cycles. Due to the difference in concentration between the surface and internal materials, the composite material exhibits a gradient memory effect during expansion and recovery. This effect allows the composite material to more flexibly adapt to changes in the surrounding environment when exposed to water or light, and maintain a more stable and accurate shape during the recovery process.

[0042] In a preferred embodiment of the present invention, in S3, the multi-stage cross-linking treatment is specifically:

[0043] Primary cross-linking treatment: Place the mixture in an oven and heat it to 40-60°C for 1-2 hours;

[0044] Secondary cross-linking treatment: Place the mixture after primary cross-linking in a vacuum oven and heat it to 60-80°C for 4-8 hours.

[0045] It should be noted that the crosslinking density and stability of the composite material are improved through multi-stage crosslinking treatment, thereby enhancing its mechanical properties and shape memory properties. After PAM and SMP are mixed, a preliminary crosslinking reaction is immediately carried out to form a preliminary crosslinking network; the mixture after the preliminary crosslinking is placed in a vacuum oven, heated and cured, and the curing time is extended to 4-8 hours under vacuum to remove bubbles and unreacted products. Additional crosslinking agents can be added at this stage to promote the secondary crosslinking reaction between SMP and PAM, further enhancing the performance of the composite material.

[0046] S4: adding a smart response substance to the mixture and continuously stirring the mixture so that the mixture can sense changes in the environment and then change, thereby obtaining a smart response mixture;

[0047] In a preferred embodiment of the present invention, in S4, the smart responder is one or more of a pH-responsive polymer and a temperature-responsive hydrogel, wherein the smart responder accounts for 5%-10% of the volume of the mixture.

[0048] It should be noted that the composite material is endowed with functional properties, namely, temperature responsiveness and light responsiveness, by introducing smart responsive additives. The smart responsive additives are uniformly added in the prepolymerization liquid of the PAM gel or the mixing stage of the SMP and PAM. The additives are uniformly distributed in the composite material by continuous stirring.

[0049] S5: Curing the smart response mixture under UV light at 60-80° C. to obtain a composite molded sheet.

[0050] It should be noted that the synergistic treatment of UV light irradiation and appropriate temperature promotes the photo-crosslinking of SMP and the further curing of PAM gel, thereby improving the performance of the composite material. During the curing process, the composite material is irradiated with UV light, which can trigger the photo-crosslinking reaction of SMP, improve the crosslinking density and shape memory performance of the composite material, and at the same time control the temperature at 60-80°C to promote the further curing of PAM gel.

[0051] When used in the present invention, polyacrylamide (PAM) is one of the main components of the composite material and has excellent water absorption and expansion properties. When the composite material meets water, the PAM matrix will quickly absorb water, resulting in volume expansion. This expansion is reversible, that is, when the water is removed, the PAM matrix will gradually return to its original state; part of the shape memory polymer (SMP) will undergo volume or shape changes under light of a specific wavelength, and under light conditions, the SMP part will expand or deform in response to light. This deformation can also be reversible, depending on the duration and intensity of the light, and the molded sheet prepared with these two materials as the matrix has the ability to expand when exposed to light or when exposed to water.

[0052] Since PAM's water absorption and expansion are isotropic, and SMP can also deform under certain conditions, the composite material can show a certain shape adaptability during the expansion process. When the composite material is placed on the surface of an irregularly shaped object, its expansion process will make the composite material gradually fit the surface shape of the object. That is, when the molded sheet is placed between the teeth of another tooth that is symmetrical to the decayed tooth (the tooth is intact), as the molded sheet expands, the outer surface of the molded sheet fits the symmetrical intact tooth, replicating the shape of the intact tooth.

[0053] The addition of nano-reinforcements not only improves the strength and toughness of composites, but may also affect their shape adaptability to a certain extent. The uniform dispersion of nano-materials helps to form a more continuous and dense matrix structure, thereby enhancing the shape memory and shape adaptability of composites.

[0054] The water absorption expansion of PAM and the photoinduced deformation of SMP are both reversible. When the light stops or the composite material is no longer in contact with water, the PAM matrix will gradually release water and return to its original state; and the SMP part will gradually return to its shape before the stimulus according to its characteristics. The multi-stage cross-linking treatment enhances the stability of the internal structure of the composite material, allowing the composite material to maintain a certain shape memory performance during the process of expansion and recovery of deformation. The cross-linking structure limits the free movement of the molecular chain, allowing the composite material to undergo controllable deformation when subjected to external stimuli, and return to the preset shape after the stimulus is removed.

[0055] Shape memory polymers (SMPs) are the key ingredients that give composite materials shape memory properties. SMPs are able to return to their preset shapes when heated or exposed to light. In composite materials, SMPs are tightly bound to the PAM matrix through a cross-linked structure, forming an overall structure with shape memory function.

[0056] When the composite material expands and deforms when it first encounters water or light and adheres to the surface of the surrounding object, even if the stimulation stops and it returns to its original state, the composite material still "remembers" the previous expansion degree and shape. This is because the molecular chains of SMP are rearranged and fixed during the deformation process, so that the composite material can quickly return to its previous expansion degree and shape when it is subjected to the same stimulation again.

[0057] When the composite material meets water again, the PAM matrix will absorb water and swell again, and the SMP part will also deform accordingly according to the previous memory state. That is, after the shape of the intact tooth is copied, and this tooth is symmetrical with the damaged tooth, the molded sheet is taken out and placed on one side of the damaged tooth, and the molded sheet is exposed to light or water again, so that the molded sheet expands and returns to the previous expanded state. Since the molded sheet copies the shape of the tooth symmetrical to the bad tooth, the empty part between the bad tooth and the molded sheet is the missing part of the bad tooth, and only the repair agent needs to be used to complete the repair of the missing part, avoiding subsequent polishing.

[0058] Embodiment 1:

[0059] The nano-reinforcement material nano-silica was dispersed in isopropanol with a nanoparticle to solvent ratio of 1:20 and treated with an ultrasonic disperser for 45 min to ensure that the nanomaterial was evenly dispersed without agglomeration.

[0060] The polyacrylamide monomer, ethanol and ammonium sulfate were mixed and polymerized under stirring conditions. The reaction temperature was controlled at 60°C, the stirring speed was 900 rpm, and the time was 50 minutes to obtain a polyacrylamide prepolymer solution.

[0061] The pretreated nano-reinforced material was added to the polyacrylamide prepolymer solution, and stirring was continued for 30 minutes to ensure that the nano-reinforced material was evenly dispersed in the polyacrylamide prepolymer solution matrix. The stirring speed was 900 rpm for 30 minutes, and the styrene-based shape memory polymer was added to the nano-reinforced material containing the polyacrylamide prepolymer solution matrix.

[0062] The ratio of nano-reinforced material particles, prepolymer liquid, and styrene-based shape memory polymer in the mixture is adjusted to 5:6:2, the concentration of styrene-based shape memory polymer is 30%, the concentration of nano-reinforced material is 10%, and the concentration of prepolymer liquid is 70% (although the surface material is designed to be rich in high concentrations of photosensitive shape memory polymer (SMP) and nanomaterials, and the inner layer is mainly polyacrylamide gel (PAM), the "high concentration" of the inner layer is actually relative to the total mass of its inner material. The "high concentration" here and the "high concentration" of the surface layer are compared within their respective material systems, not directly comparing the absolute concentration values ​​of the surface layer and the inner layer). The SMP and nano-reinforced material are injected into the cavity in the mold through the injection molding technology, and the gel mainly composed of PAM is injected into the middle hollow of the placeholder plate to obtain a gradient mixture, which is cross-linked. The distribution of the shape memory polymer and the nano-reinforced material in the composite material is controlled through the injection molding technology to form a gradient structure that gradually changes from the surface to the inside. The surface layer can be designed as a high-concentration layer rich in photosensitive shape memory polymers and nanomaterials, while the interior is a low-concentration layer mainly composed of polyacrylamide gel. The placeholder plate is then removed and a cross-linking reaction is carried out.

[0063] Primary cross-linking: After the polyacrylamide and the shape memory polymer are mixed, a preliminary cross-linking reaction is immediately carried out, the temperature is controlled at room temperature to 60°C, and the time is 1.5 hours.

[0064] Secondary crosslinking: The mixture after the preliminary crosslinking was placed in a vacuum oven and heated and cured at 70°C for 6 hours, while the vacuum degree was adjusted to remove bubbles and unreacted products. Additional crosslinking agent was added to promote the secondary crosslinking reaction between the shape memory polymer and the polyacrylamide.

[0065] During the prepolymerization of polyacrylamide gel or the mixing stage of shape memory polymer and polyacrylamide, pH-responsive polymer and temperature-responsive hydrogel are uniformly added to ensure their uniform distribution in the composite material, and the smart responder accounts for 7% of the volume of the mixture.

[0066] In the curing and molding stage, UV light irradiation and a temperature of 70° C. are used in synergistic treatment to promote the photo-crosslinking of the shape memory polymer and the further curing of the polyacrylamide gel, thereby obtaining a composite molding sheet.

[0067] Experiment 1:

[0068] The preparation method in Example 1 was used as Experimental Group 1, and the surface concentration and internal concentration of the composite material in the preparation process of Example 1 were changed respectively to serve as several control groups. The molded sheets prepared in Experimental Group 1 and several control groups were placed in the gap between two intact teeth, and the molded sheets were irradiated and water was added to deform the molded sheets to fit the teeth. Then the irradiation and water addition were stopped to restore the deformation. After that, the molded sheets were irradiated and water was added again to restore the deformation to the previous degree. Since the teeth here are intact and the position of the molded sheet has not been moved, it is only necessary to observe the size of the gap between the molded sheet and the teeth. See Table 1 for details.

[0069] Table 1

[0070]

[0071] In summary, it can be seen that in the control group one, the molded sheet prepared by the ordinary method will have large gaps during use, and a large amount of space will be required to grind off the excess repair agent after the repair is completed. In the control groups two to six, the concentrations of nano-reinforced materials, prepolymers and shape memory polymers were adjusted respectively, and then gradient concentrations were prepared. By comparison, it was found that only when the surface layer was designed as a high-concentration layer rich in photosensitive SMP and nanomaterials and the interior was a low-concentration layer mainly composed of PAM gel, the prepared material can more flexibly adapt to changes in the external environment, ensuring a more stable and accurate shape during the recovery process.

[0072] Experiment 2

[0073] The preparation method in Example 1 was used as Experimental Group 2, and the preparation process in the cross-linking stage of Example 1 during the preparation process was changed to serve as several control groups, and the molded sheets prepared in Experimental Group 2 and several control groups were used to repair teeth with damaged corners, and the molded sheets were placed at the gap between another intact tooth symmetrical to the damaged tooth, and the molded sheets were stimulated to expand and fit the intact tooth, and the stimulation was stopped, and the molded sheets recovered their deformation, and the molded sheets were taken out and placed at the damaged tooth, and the molded sheets were stimulated again, and the molded sheets recovered the degree of expansion of the previous time, and the restorative agent was directly filled, and the repair time and degree of repair were recorded, as shown in Table 2 for details.

[0074] Table 2

[0075]

[0076] In summary, it can be seen that the control group seven was prepared using the normal method of preparing the molding sheet, and the resulting molding sheet could not fit well with the defective part of the tooth, and the excess part needed to be trimmed and polished off after the repair was completed. The control groups eight and nine directly and continuously used a strong cross-linking environment to make it cross-link quickly and continued to use a relatively mild method for cross-linking, respectively. It was found that both would make the layering and strength of the cross-linking of the prepared molding sheet too strong or too weak during the cross-linking process, resulting in poor shaping ability. Therefore, slight trimming and polishing are still required in the later process of tooth repair. Only the control group ten and the experimental group two used a mild cross-linking method for cross-linking during the primary cross-linking process, and then transitioned to a strong cross-linking environment in the subsequent secondary cross-linking process, which not only deepened the layering and strength of the cross-linking network, but also removed all impurities and bubbles that may interfere with shape memory through vacuum technology.

[0077] The above is based on the ideal embodiment of the present invention. Through the above description, relevant personnel can make various changes and modifications without departing from the technical concept of the present invention. The technical scope of the present invention is not limited to the content in the specification, and the technical scope must be determined according to the scope of the claims.

Claims

1. A composite molding sheet for filling, characterized in that: The following steps are involved: S1: mixing nano-reinforcement material particles with a solvent and performing ultrasonic dispersion treatment to obtain a nano-reinforcement material solution; S2: Select a material that swells when exposed to water, prepare it into a prepolymer solution, mix it with a nano-reinforced material, stir it to obtain a matrix material, add a shape memory polymer and continue stirring to obtain a mixture; S3: adjusting the ratio of nano-reinforced material particles, prepolymer liquid and shape memory polymer in the mixture, injecting them into the mold through injection molding technology to obtain a gradient mixture, and performing cross-linking treatment; S4: adding a smart response substance to the mixture and continuously stirring the mixture so that the mixture can sense changes in the environment and then change, thereby obtaining a smart response mixture; S5: Curing the smart response mixture under UV light at 60-80° C. to obtain a composite molded sheet.

2. A composite forming sheet for filling according to claim 1, characterized in that: In S1, the nano-reinforcement material particles are selected from one or more of nano-silicon dioxide, nano-cellulose or nano-clay, the solvent is selected from one or more of isopropanol weak alkaline aqueous solution or methanol, the ratio of nano-particles to solvent is 1:10-30, and the ultrasonic dispersion treatment time is 30-60 minutes.

3. The composite forming sheet for filling according to claim 1, characterized in that: In S2, the water-swellable material is selected from one or more of polyacrylamide, calcium carbonate or barium carbonate, the amount of nano-reinforced material added is 10%-20% of the total volume of the prepolymer solution, the stirring speed is 800-1000 rpm, and the time is 20-40 min.

4. The composite forming sheet for filling according to claim 1, characterized in that: In S2, the preparation of the prepolymer solution is specifically to mix the water-swellable material with a solvent and a catalyst, and to carry out a polymerization reaction under stirring.

5. A composite forming sheet for filling according to claim 4, characterized in that: The solvent is selected from one or more of ethanol, dilute nitric acid or hydrochloric acid, the catalyst is selected from one or more of ammonium sulfate, alkaline catalyst or acid catalyst, the stirring speed is 800-1000 rpm, and the time is 30-60 min.

6. The composite forming sheet for filling according to claim 1, characterized in that: In S2, the shape memory polymer is selected from one or more of styrene-based shape memory polymer, polyimide-based shape memory polymer or cyanate-based shape memory polymer, wherein the added amount of the shape memory polymer is 20%-30% of the base material.

7. The composite forming sheet for filling according to claim 1, characterized in that: In S4, the smart responder is one or more of a pH-responsive polymer and a temperature-responsive hydrogel, wherein the smart responder accounts for 5%-10% of the volume of the mixture.

8. The composite forming sheet for filling according to claim 1, characterized in that: In the S3, the ratio of nano-reinforcement material particles, prepolymer solution and shape memory polymer is 1-10:3-7:1-5.

9. The composite forming sheet for filling according to claim 1, characterized in that: In S3, the mold includes a cavity and a placeholder plate plugged into the cavity, the cavity is provided with an elliptical cavity with a flat cross-section, which is used to inject high-concentration shape memory polymers and nano-reinforced materials, the placeholder plate is arranged at the center of the cavity, the placeholder plate can be taken out, and after being taken out, a low-concentration prepolymer liquid can be injected.

10. The composite forming sheet for filling according to claim 1, characterized in that: In S3, the multi-stage cross-linking treatment is specifically: Primary cross-linking treatment: Place the mixture in an oven and heat it to 40-60°C for 1-2 hours; Secondary cross-linking treatment: Place the mixture after primary cross-linking in a vacuum oven and heat it to 60-80°C for 4-8 hours.